2010
DOI: 10.1016/j.jmwh.2009.05.006
|View full text |Cite
|
Sign up to set email alerts
|

The Long‐Term Effects of Prenatal Nicotine Exposure on Neurologic Development

Abstract: A large body of documented evidence shows that smoking during pregnancy is harmful to both the mother and fetus. Prenatal exposure to nicotine in various forms alters neurologic development in experimental animals and may increase the risk for neurologic conditions in humans. There is a direct association between maternal smoking and SIDS; however the connection with depression, attention disorders, learning and behavior problems, and nicotine addiction in humans is not straightforward. Nicotine’s action on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 79 publications
0
59
0
3
Order By: Relevance
“…Maternal smoking is a risk factor for many psychiatric disorders (Blood-Siegfried and Rende, 2010;Button et al, 2007;Ernst et al, 2001;Fried and Watkinson, 2001;Jacobsen et al, 2007;Milberger et al, 1996Milberger et al, , 1998Pauly and Slotkin, 2008;Schmitz et al, 2006;Thapar et al, 2003;Tong and McMichael, 1992) and is still a common practice according to Substance Abuse & Mental Health Services which reported in 2012 that one in five women smoke during pregnancy. In addition to being an important issue in its own right, prenatal nicotine exposure has gained considerable traction as a suitable model for impulsive behavior as seen in ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal smoking is a risk factor for many psychiatric disorders (Blood-Siegfried and Rende, 2010;Button et al, 2007;Ernst et al, 2001;Fried and Watkinson, 2001;Jacobsen et al, 2007;Milberger et al, 1996Milberger et al, , 1998Pauly and Slotkin, 2008;Schmitz et al, 2006;Thapar et al, 2003;Tong and McMichael, 1992) and is still a common practice according to Substance Abuse & Mental Health Services which reported in 2012 that one in five women smoke during pregnancy. In addition to being an important issue in its own right, prenatal nicotine exposure has gained considerable traction as a suitable model for impulsive behavior as seen in ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, this result may indicate the presence of an unaccounted-for mediator, potentially one involving time delays that could explain the late emergence of MSP's effect during young adulthood. One likely candidate is MSP's direct teratologic effects on the developing brain (Wakschlag et al, 2002): MSP may cause epigenetic changes (Toledo-Rodriguez et al, 2010) and disrupt neural development (Dwyer, McQuown, & Leslie, 2009) in a way that results in a long-term abnormal response to nicotine (Blood-Siegfried & Rende, 2010;Gold, Keller, & Perry, 2009;Slotkin, Tate, Cousins, & Seidler, 2006). If the development of these neural pathways is still incomplete during adolescence, the effects of MSP may not manifest until young adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…These reviews have reported relatively consistent links between MSDP and neurobehavioral deficits but highlight the difficulty in establishing causal associations given the number of potentially confounding factors, ethical impossibility of experimental designs in humans, and obstacles in translating findings from animal models to human neurobehavioral outcomes. Previous reviews have also summarized associations between MSDP and offspring neural development with focus on both animal and some human studies (Baler et al, 2008;Blood-Siegfried & Rende, 2010;Dwyer et al, 2009;Shea & Steiner, 2008;Slotkin, 1998). These reviews suggest that dysregulation in the development of receptor, neurotransmitter, and basic synaptic systems by maternal smoking/prenatal nicotine could lead to functional and structural brain changes and neurobehavioral/cognitive impairments in offspring.…”
Section: Introductionmentioning
confidence: 99%